Quantum Interference in Wilkinson Power Dividers (Laser Photonics Rev. 16(8)/2022). Issue 8 (9th August 2022) - Hernández, Osmery; Ortega‐Gomez, Angel; Bravo, Mikel; Liberal, Iñigo
Abstract : Photonic Quantum Networks Scaling up quantum technologies will require new ideas at the device and systems levels. In article number 2200095, Osmery Hernández and colleagues demonstrate that Wilkinson power dividers (WPDs) reduce the complexity of coherent perfect absorption (CPA) photonic quantum networks, leading to smaller footprints and a reduced number of elements. The image illustrates integrated photonics WPD supporting CPA and perfect transparency of entangled photons.